CASE STUDY IN THE BENJAMIN CONSTANT COMMUNITY IN BRAGANÇA- PARÁ: AN ANALYSIS OF TERRITORY IN RURAL SPACE (1894-2024) - da Silva Matos, Juliana (Revista Gênero e Interdisciplinaridade, 2025)
This paper analyzes the geographic and territorial formation of the Benjamin Constant community, located in the municipality of Bragança-PA. Founded in 1894 as a colonial center, it received Spanish and Northeastern immigrants to promote agriculture and supply the capital, Belém. Using quantitative and qualitative methodology and case study, the research investigated, through interviews, questionnaires and bibliographical survey, the territorial and socioeconomic transformations of the community. Three his- torical cycles shaped the territory: railway (1908–1964), road (from 1956) and electric (from 2008). The closure of the railway caused isolation, rural exodus and population decline - today with only 127 residents. Despite this, family farming persists, adapting to market demands, such as the Geographical Indication of Bragança flour. The study highlights challenges such as precarious infrastructure, lack of public policies and loss of territorial identity, contrasting with the cultural and productive resistance of the residents. It concludes that valuing local history and strengthening family farming are essential for sustainable development and the permanence of families in the countryside.